The Rural/Urban Wage Gap in the Industrialisation of Russia, 1884-1910. - Borodkin, L; Granville, B; Leonard, C (Cambridge University Press, 2008)
This article presents econometric evidence of integration in rural and urban wages in Russia's Northwest in the late tsarist era. Using the Autoregressive Distributed Lag (ARDL) approach to co-integration and error correction modelling, we show the flexibility of the rural wage in response to the lagged rural/urban wage ratio. Applying the model developed by Boyer and Hatton (1994) and Hatton and Williamson (1991a, 1991b, 1992), we show the similarity of the wage gap in northwest Russia in the late tsarist era to that during industrialisation in the US, England and Western Europe. Although our evidence does not necessarily describe countrywide trends, it does support for an industrialising region the more positive view of the degree and nature of late tsarist economic growth. Growth was not slowing down, and there is little evidence of constraints on migration by traditional agrarian institutions.